ChemInform Abstract: Organocatalytic Asymmetric Michael Addition/Carbon—Carbon Bond Cleavage of Trifluoromethyl α‐Fluorinated gem‐Diols to Nitroolefins. Issue 32 (18th July 2013) - Saidalimu, Ibrayim; Fang, Xiang; Lv, Wenwen; Yang, Xueyan; He, Xiaopeng; Zhang, Jingyuan; Wu, Fanhong
Abstract Low yields and diastereoselectivity is observed for the substrates bearing aliphatic substituents.